A decade of hospitalizations for hyperthyroidism in the US. Issue 6 (2nd November 2022) - Shaka, Hafeez; Salim, Michael; DeHart, Luke; El-amir, Zain; Wani, Farah; Kichloo, Asim
Abstract: The goal of this study was to examine healthcare burden, hospitalizations, mortality, and healthcare cost utilization from hyperthyroidism to further our understanding of the effect of changes in thyroid disease management over the past decade. This was a retrospective longitudinal trends study involving hospitalizations for hyperthyroidism in the US from 2008 to 2018. We trended crude hospitalization rate, estimated incidence of hospitalizations, trends in inpatient mortality rate, mean length of hospital stay, and mean total hospital cost of patients with hyperthyroidism. The number of hyperthyroid hospitalizations decreased from 12, 689 in 2008 to 9110 in 2018 (28.2%) ( P trend <0.001), with a decrease of crude hospitalization rate from 33 to 25 per 100, 000 hospitalizations. The estimated incidence rate of hospitalization in patients with hyperthyroidism decreased from 441 to 288 per 100, 000 adults with hyperthyroidism. There was, however, no difference in adjusted mortality in hospitalizations over the study period. Although there has been a significant reduction in hospitalizations due to hyperthyroidism in the US, there has been no significant change in mortality during hospitalizations. This may represent improving outpatient management of hyperthyroidism. However, this improvement has not translated to outcomes in the hospital setting.